SELF MEDICATION PRACTICE AMONG MEDICAL, PHARMACY AND NURSING STUDENTS - Johnson, Deena; Sekhar, Hima S.; Alex, Teena; Kumaraswamy, M.; Chopra, Rajveer Singh (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The main objective of this study was to identify the commonly used drugs, indications, reasons, factors and to assess the attitude of medical, pharmacy and nursing students towards self-medication. Methods: A prospective cross-sectional study was carried out in students of Medical, Pharmacy and Nursing college of Adichunchanagiri Institutions B. G Nagara from October 2014 to March 2015. Relevant information was obtained by using the questionnaire after taking the consent from students. The obtained data were analyzed by SPSS version 17.0. Results: 736 students were enrolled in the study, with the age group of 17-26 y. In that 516 (70.1%) were females, 220 (29.9%) were male students. Females were self-medicating more (96.5%) than males (89.54%). The most common drugs used as self-medication are antipyretics (83.15%), antihistamines (26%), analgesics (25%). Fever and headache are the most common illness for self-medication reported. Among the reasons for self-medication, 86.54% students were reported that they used self-medication due to lack of time to consult the physician, 54.89% and 54.07% were reported that they felt their health problem is not serious and for their quick relief respectively. Conclusion: Study concluded that the prevalence of self-medication practice is more among the medical and paramedical students because they are having easy access to knowledge related to the diseases and drugs. Among the three groups of students the prevalence of self-medication is more among nursing students. Keywords: Self-medication, Over the counter drug, NSAIDS